Enhancing photocatalytic degradation of the cyanotoxin microcystin-LR with the addition of sulfate-radical generating oxidants - Antoniou, Maria G.; Boraei, Iosef; Solakidou, Maria; Deligiannakis, Yiannis G.; Abhishek, Mahalakshmi; Lawton, Linda; Edwards, Christine (My University, 2018)
This study investigated the coupling of sulfate radical generating oxidants, (persulfate, PS and peroxymonosulfate, PMS) with TiO2 photocatalysis for the degradation of microcystin-LR (MC-LR). Treatment efficiency was evaluated by estimating the electrical energy per order (EEO). Oxidant addition at 4 mg/L reduced the energy requirements of the treatment by 60% and 12% for PMS and PS, respectively compared with conventional photocatalysis. Quenching studies indicated that both sulfate and hydroxyl radicals contributed towards the degradation of MC-LR for both oxidants, while Electron Paramagnetic Resonance (EPR) studies confirmed that the oxidants prolonged that lifetime of both radicals (concentration maxima shifted from 10 to 20 min), allowing for bulk diffusion and enhancing cyanotoxin removal. Structural identification of transformation products (TPs) formed during all treatments, indicated that early stage degradation of MC-LR occurred mainly on the aromatic ring and conjugated carbon double bonds of the ADDA amino acid. In addition, simultaneous hydroxyl substitution of the aromatic ring and the conjugated double carbon bonds of ADDA (m/z = 1027.5) are reported for the first time. Oxidant addition also increased the rates of formation/degradation of TPs and affected the overall toxicity of the treated samples. The detoxification and degradation order of the treatments was UVA/TiO2/PMS > UVA/TiO2/PS>> UVA/TiO2.
Keywords: Cyanotoxins; Intermediates; Peroxymonosulfate; Persulfate; TiO2photocatalysis